Islamic Religious Education Teacher's Strategy in Instilling the Value of Religious Nationalism with Islamic Tsaqofah Subjects - Bilal, Muhamad (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
This research aims to describe teachers' strategies in instilling the values of religious nationalism in the Tsaqofah Islamiyah subject at the Integrated Islamic Senior High School (SMAIT) Al Hikmah Boyolali. This research employs a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation. The results indicate that in implementing the inculcation of religious nationalism values, Islamic Religious Education (PAI) teachers, particularly in the Tsaqofah Islamiyah subject, create a school culture, serve as role models, and instill values both inside and outside the learning environment. The strategies used include linking Quranic verses related to nationalism, associating the history of Muslim struggles with Indonesia's independence, actively involving students in learning activities, and applying direct practice through assignments both inside and outside the school. Additionally, Pancasila values are integrated into the learning process to provide a deeper understanding of its history and significance. Through these strategies, students exhibit religious nationalism reflected in their love and pride for Indonesia, as well as in their honesty, discipline, responsibility, sincerity, independence, care, hard work, justice, and courage. This study highlights the crucial role of Islamic religious education in shaping students' character based on religious nationalism values. The results of this study show that the strategies implemented by teachers effectively instill religious nationalism values in students, as reflected in their attitudes and daily behavior.